Screen schooled - "Clement, Joe" (Black Inc. Carlton, 2018)
Veteran teachers Joe Clement and Matt Miles have seen firsthand how damaging technology overuse and misuse has been to our kids. On a mission to educate and empower parents, they show how screen saturation at home and school has created a wide range of cognitive and social deficits in our young people. They lift the veil on what's really going on? in schools- teachers who are often powerless to curb distractions from electronic devices; zoned-out kids who act helpless and are unfocused, unprepared, and unsocial; administrators who are influenced by questionable science sponsored by corporate technology purveyors. Clement and Miles suggest steps parents can take to demand change? and they make a compelling case for simpler, smarter, more effective forms of teaching and learning